A bio-based and non-toxic polyurethane film derived from Luffa cylindrica cellulose and ʟ-Lysine diisocyanate ethyl ester. (5th December 2021) - Akay, Ozge; Altinkok, Cagatay; Acik, Gokhan; Yuce, Huseyin; Ege, Gozde Konuk
Graphical abstract: Highlights: The cellulose extracted from Luffa cylindrica can be utilized for synthesizing different polyurethane architectures. The combined treatment applied on raw Luffa cylindrica causes to increase in hydrophilicity, thermal stability and transition temperatures. The incorporation of ʟ-Lysine diisocyanate ethyl ester on cellulose of Luffa cylindrica enhances hydrophobicity, thermal properties and biodegradability. The PUR film achieved is degradable in enzymatic and hydrolytic conditions. Abstract: This study aims to explore the step-growth polymerization (SGP) between the most abundant biomass-cellulose (LCC) extracted from Luffa cylindrica (LC) and ʟ-Lysine diisocyanate ethyl ester (ʟ-LDI) to be achieved an unprecedented polyurethane network (PUR). The resulting bio-based and non-toxic PUR film is obtained by direct solution casting after SGP. The efficiency of the SGP is examined in detail Fourier transform infrared (FT-IR) and proton nuclear magnetic resonance ( 1 H NMR) spectroscopies, water contact angle (WCA) measurements, thermogravimetric and differential scanning calorimetry analyses (TGA and DSC) by comparing precursors and final film. Moreover, the biodegradation behavior of PUR achieved is evaluated in vitro both hydrolytic and enzymatic media. Based on the conducted analyses, PUR film shows higher hydrophobicity and degradation temperatures compared to raw LC and LCC. Moreover, it is determined that the PUR film more degradable than its precursors in both hydrolytic and enzymatic media. Consequently, the approach developed here is broadly adaptable to other functional isocyanate monomers and will be useful to scientists working on bioplastic applications.